Candidate Species for Florida Aquaculture: Evaluating an Aquatic Organism's Aquaculture Potential - Cortney L. Ohs; R. LeRoy Creswell (EDIS)
FA146, a 5-page fact sheet by Cortney L. Ohs and R. LeRoy Creswell, introduces a series detailing the potential of different aquatic organisms for aquaculture in Florida. It defines and describes important characteristics of aquatic species and discusses how these characteristics affect a species' aquaculture potential. Published by the UF Department of Fisheries and Aquatic Sciences, June 2007.